Ethical Attitude and Perception of Accounting Students in Preparing Financial Statements (Case Study on Accounting Students in Faculty of Economic and Business Tanjungpura University) - B1034141008, Meza Rovianti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ETHICAL ATTITUDE AND PERCEPTION OF ACCOUNTING STUDENTS IN PREPARING FINANCIAL STATEMENTS(Case Study on Accounting Students in Faculty of Economic and Business Tanjungpura University)by:                                                                                                                               Meza RoviantiFaculty of Economics and Business, Accounting Departement Tanjungpura UniversityABSTRACTOne of the factors that still need to be improved the quality of financial reporting in Indonesia is related to the ethics and positive attitude of Indonesian accountants. With a variety of reasons and goals, either true or false, sometimes the presentation of financial statements that have been made by the accountant deviates from the ethics and positive attitude of an accountant. It is not surprising that ethics has always highlighted accountants in presenting financial statements.The purposes of this study to find out the influence of ethical attitudes of accounting students in preparing financial statements, To find out the influence of perceptions of accounting students in preparing financial statements and To find out the influence of ethical attitudes and perceptions of accounting students in preparing financial statements.The data used is primary data. In this study, the author uses a questionnaire as a data collection tool. Data processing is assisted with SPSS 23.             The results of this study show that the ethical attitude partially does not have a significant effect, perception partially has a significant influence and then the ethical attitudes and perceptions do not have a significant relationship simultaneously. Keywords: ethical, attitude, perception, accounting students, financial statement.